Interaksi Fonologi dan Morfologi dalam Pembentukan Kata Dan Kalimat Bahasa Indonesia: Kajian Literatur Sistematis - Novianti, Silvina; Fauziah, Laili; Hutasoit, Danada Murni Br (Indo-MathEdu Intellectuals Journal, 2025)
This study systematically reviews the interaction between phonology and morphology in the formation of Indonesian words and sentences. Indonesian, as an agglutinative language, demonstrates productive affixation processes and systematic phonological mechanisms such as assimilation, elision, and reduplication. This article synthesizes recent scholarly findings to explain how phonological processes influence morphological constructions and how both systems operate together at the morpheme, word, and sentence levels. The methodology employed follows a systematic literature review framework by identifying, selecting, synthesizing, and analyzing empirical studies published in the last decade. Findings show that nasal assimilation, affix productivity, and adaptation of loanwords are central mechanisms shaping Indonesian word formation. In digital communication, phonological reduction and innovative morphological adaptations are increasingly visible. The study concludes that phonology and morphology are inherently interconnected and mutually influence linguistic structure and usage, especially in contemporary digital contexts.